Immediate and substantial evolution of T-cell repertoire in peripheral blood and tumor microenvironment of patients with esophageal squamous cell carcinoma treated with preoperative chemotherapy. (7th September 2018) - Zhang, Chaoting; Palashati, Heyilimu; Tan, Qin; Ku, Wenjing; Miao, Yu; Xiong, Hongchao; Lu, Zheming
Abstract: Preoperative chemotherapy could decrease tumor size and improve overall survival for esophageal squamous cell carcinoma (ESCC), and moreover, rational combination of chemotherapy and immunotherapy could increase likelihood of inducing an effective antitumor immune response. However, the immunologic impact of chemotherapeutic drugs originally chosen for cancer treatment due to the direct toxicity is poorly understood. We assess the effect of a combination of clinically approved chemotherapeutic drugs [paclitaxel–nedaplatin (PTX–NDP)] on T-cell receptor (TCR) repertoires of peripheral T cells and tumor-infiltrating lymphocytes (TILs) from five patients with primary ESCC. We found that PTX–NDP therapy induced immediate and substantial changes in clonotype frequencies of peripheral T cells and TILs, and moreover, compared with clonal amplification, clonal contraction was more likely to occur in more abundant clones in patients with ESCC. Significant increases in TCR diversity were observed in peripheral T cells but not in TILs after PTX–NDP therapy. Reconstruction of posttreatment TILs was not merely a result of local expansion or contraction of pretreatment TILs, but also—at least in part—a consequence of the migration of peripheral T cells into the chronically inflamed tumor microenvironment. Our findings uncover further insight into T-cell immune response modulated with chemotherapy, providing for theoretical bases for rational combination strategy of chemotherapy and immunotherapy. Abstract : PTX-NDP therapy induced substantial changes in clonal distribution of peripheral T cells and TILs and additionally reconstruction of post-treatment TILs was contributed by local variations of TILs and migration of peripheral T cells.